External quality control program: Experience in the department of Microbiology and Immunology, Muhimbili University College of Health Sciences, Dar es Salaam, Tanzania (Tanzania Medical Journal, 2007)
Objective: To share experiences and lessons learned from 2002 National External Quality Assessment Schemes for Leukocyte Immunophenotyping (UK NEQAS) and College of American Pathologists (CAP) proficiency testing (PT) panels received and tested as part of External Quality Control ProgramSetting: Department of Microbiology and Immunology, Muhimbili University College of Health Sciences, Dar es Salaam.Methods: All PT panel records from January – December 2002 were reviewed and summarized to show the type of panel and date received, date results sent after analysis and our performances.Results: Six and fourteen panels were received from UKNEQAS and CAP, respectively. The mean time interval between receipt of panels and reporting back of the results was 9.4 days (range 2-17). UKNEQAS performance was good in 5/6 panels (83.3%) analyzed. Among CAP panels, satisfactory (100%) performances included two viral markers, two C. trachomatis antigen detection and two comprehensive hematology with automated differentials whereas unsatisfactory (79%, 66%, 71%) performances were all 3 general chemistry with an overall score of (6/9) 66.7%. Conclusion: To implement an effective and efficient quality assurance in an established laboratory requires committed long-term efforts that are potentially constrained with multiple obstacles. Continuing education and training of laboratory personnel is an integral part of quality control/quality assurance program. Keywords: Proficiency Testing, Quality Control, and Quality Assurance. > Tanzania Medical Journal Vol. 19 (1) 2004